Letter: ACE2, IBD and COVID‐19—why IBD patients may be at reduced risk of COVID‐19. Issue 8 (20th September 2020) - Prentice, Ralley E.; Tjandra, Doug; Garg, Mayur; Lubel, John S.; Fourlanos, Spiros; Johnson, Doug; Al‐Ani, Aysha; Christensen, Britt
Abstract : LINKED CONTENT This article is linked to Taxonera et al paper. To view this article, visit https://doi.org/10.1111/apt.15804